Economic Order Quantity (EOQ) Method Analysis, ABC Classification and Vital, Essential and Non Essential (VEN) Analysis of Medicines - Inayah Inayah; Benny Alexandri; Meita Pragiwani (BPJP - STEI, 2022)
This study aims to analyze the economic order quantity (EOQ) method, ABC classification as well as vital, essential and non-essential (VEN) analysis of drug supplies, to determine trends in the supply of vital (V), essential (E) and non-essential (N), to determine the frequency of purchasing drug preparations and the optimal amount of drug needs and to determine the total cost of supplies at the Dharma Pharmacy Clinic, Tangerang. This study used a quantitative descriptive method and interviews were analyzed using QM software for Windows V. From the research and calculations, the results obtained, in the analysis of vital (V), essential (E) and non- essential (N) classifications of 160 drug units classified as 66 units of vital drug classes, 58 units of essential drugs and 36 units of non-essential groups. In the use of the ABC classification analysis based on the investment value, it can be seen that group A from the vital drug group is 69.83% with a volume of 17 units, the essential drug group is 70.23% with a volume of 13 units and the non-essential group is 70.69% with a volume of 6 units. Group B of the vital drug group was 20.16% by volume 18 units, the essential drug group was 19.24% with a volume of 14 units and the non-essential group was 17.88% with a volume of 7 units. Group C vital group 10.01% volume 31 units, essential 10.53% by volume 31 units and 9.48% non essential group with volume 23 units. With the EOQ method in the procurement of drug preparations, the cost of purchasing a drug unit for a class of vital drugs is Rp. 1,069,223,104 with the lowest EOQ value of 1 and the highest is 105, for the essential drug class of Rp. 280,472,456, the lowest EOQ value is 1 and the highest is 41, and the non- essential drug class is Rp. 148,042,836 with the lowest EOQ value of 1 and the highest of 58.